Public Awareness, Perception and Attitude Towards Epilepsy in Greater Chittagong (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Epilepsy is generally perceived negatively as a lifelong, incurable disorder and is frequently thought of a punishment of evil deeds. To the best of my knowledge no data is yet published in Bangladesh. People should be aware of epilepsy in order to proper management of acute stage and used of antiepileptic drugs and its duration. This study strives to evaluate the public awareness, perception and attitudes toward epilepsy in Chattogram. Materials and methods: This was a cross sectional descriptive study conducted during the period from November 2012 to October 2013. Initially 474 attendants in Department of Pediatrics and Neonatology of Chattagram Maa Shishu O General Hospital, Chittagong Medical College Hospital & University of Science and Technology Chittagong were included, of them 90 patients did not hear the term epilepsy, so no further question has made. Rests of 384 were selected as sample from study population. Results: Result of all 384 respondents could be analyzed. About the awareness regarding epilepsy among 384 respondents, 52.1% believed that epilepsy is mental illness, 83.59% witnessed seizure - which reflect that level of awareness is moderate. 47.14% respondents seemed that epilepsy is inherited, 63.54% resolved that epilepsy can be cured- which reflect that level of perception is moderate. 67.19% respondents regarded that medication for seizure should take regularly, 52.08% supposed that epilepsy patients were discriminated 31.25% by School mates, 7.81% by their teachers, 13.02% by their spouse which reflect that level of attitude is moderate. Conclusion: Awareness, perception and attitude is moderate in level regarding epilepsy in greater Chattogram.Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 22-26